PERUBAHAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI YANG MELAKUKAN SENAM HIPERTENSI - M Ivan Zeaul Alhaq; Nurul Hidayah; Lucia Retnowati (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
Hypertension is a health problem that is quite dangerous throughout the world because hypertension is a major risk that leads to cardiovascular diseases such as heart attack, heart failure, stroke and kidney disease. As a person ages, the risk of hypertension increases that the walls of blood vessels will lose their elasticity. Hypertensive gymnastics is a sport that aims to increase blood flow and oxygen supply to the muscles and skeleton that are active, especially to the heart muscle. This literature study aims to determine changes in blood pressure in elderly patients with hypertension who do hypertension exercise. The Study Literature method is a Systematic Literature Review, in this Study Literature using 5 research journals sourced from the Google Schoolar database. The results obtained from the analysis of 5 selected journals indicate that there is an effect of hypertension exercise on reducing systolic and diastolikic pressure in the elderly with hypertension, the earlier and regularly the hypertension patient performs the exercise, the more significant the blood changes are shown. It is expected for the elderly to apply hypertension exercise before the hypertension level increases and the age increases. For further researchers, it is hoped that they will be able to develop research with new themes and increase information, references, and insights in using Literature Review as a reference for compiling the final project